Study on Human Cranial Index with its Sex Difference from Central Kerala - Kaithackal, Jameskutty Baby Jacob; George, Anne; Raveendran, Renju (Asian Journal of Medical Sciences, 2021)
Background: Cranial index, primarily used as an indicator of race had been studied by various workers in view of its morphometric difference in sex prediliction. Hence it would be useful to identify sex of an individual from skeletal remains. Similar studies from our geographic region, if at all present might be very few. Aims and Objective: Based on maximum breadth and length of skull the study aimed at whether there was any statistically significant difference in the cranial index of male and female. Materials and Methods: We used 96 dry,intact skulls preserved in the departments of Forensic Medicine and Anatomy of various Medical Colleges in Kottayam, Ernakulam, Alappuzha and Pathanamthitta districts of Kerala state, India. Skull typed as male or female by observation method was measured for its maximum breadth and length, cranial index derived and the data was entered against corresponding serial number. The data analysis was conducted using SPSS software. Results: The mean percentage values of cranial index for female and male were respectively 77.68±4.53 and 73.71±4.05 with the p-value noted as 0.0001from their ranks determined by Mann- Whitney U test which showed statistically significant difference in cranial index of the two sexes. Literature could reveal similar results in studies conducted by other authors. Conclusion: Hence this morphometric study proved that it is valuable to include the application of cranial index in the identification procedure of skeletal remains. Further metric studies in this field are needed with a wider usage of other indices.